What You Should Know About Heat Straightening Repair of Damaged Steel - Avent, R. Richard; Mukai, David J. (Engineering Journal, 2001)
The repair of damaged steel through the application of heat has long been considered an art rather than a science. As such both the methodology and results have varied considerably from one practitioner to another. Because steel tends to be a forgiving material, successful repairs outnumber failures. Yet material properties may be compromised resulting in a weakened in-place structure. In addition, it is not unusual for a fracture to occur during the repair process. As a result, the use of heat straightening (or flame straightening) has had limited application. Many engineers are reluctant to allow heat straightening because of the lack of an established method of application as well as the lack of quantification of steel properties after the repair is complete. The purpose of this paper is to provide some engineering guidelines for use of the heat-straightening process.